PENGARUH PENGETAHUAN PAJAK, SANKSI PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK PBB-P2 (Studi Kasus Desa Baturetno, Kecamatan Baturetno, Kabupaten Wonogiri) - Adi Putri Nur Rohmah; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the effect of tax knowledge, tax sanctions, taxpayer awareness, and quality of tax fiscus on PBB-P2 taxpayer compliance. The study variables consist of four independent variables and one dependent variable. Independent study variables include tax knowledge, tax sanctions, taxpayer awareness, and quality of tax fiscus. The dependent variable of the study consists of taxpayer compliance. The study population is the taxpayers of Rural and Urban Land and Building Tax in Baturetno Village, Wonogiri Regency, Central Java. Sampling technique using convenience sampling which is calculated by the Slovin Formula and get a sample of 150 respondents. Data collection technique was carried out by direct surveys through questionnaires. Analysis using multiple linear analysis method with SPSS 26.0. The results showed that all independent variables: tax knowledge, tax sanctions, taxpayer awareness, and the quality of tax fiscus have a positive and significant effect on taxpayer compliance.